Tectonic evolution and its control on oil–gas accumulation in southern East China Sea since the Jurassic - Wang, Mingjian; Jiang, Xingchao; Lei, Baohua; Huang, Long; Pan, Jun (Frontiers in Earth Science, 2023)
Based on the results from the previous research on Mesozoic igneous rocks, as well as tectonic environments in the northern South China Sea and southern East China Sea (NSCS-SECS), geophysical parameters, strata, and characteristics of seismic facies in NSCS-SECS were investigated. These findings were combined with results from the analysis of the balanced profile evolution to re-evaluate the tectonic evolution of SECS since the Jurassic. Furthermore, burial history and simulation of wells in the SECS were analyzed using well, seismic and source rock data. Furthermore, favorable models of oil–gas accumulation in the Lower–Middle Jurassic were proposed in combination with studies on elements and conditions of the petroleum system. The results demonstrated that the NSCS-SECS had consistent tectonic settings and comparable strata from the Jurassic to the Cretaceous time. There was a large unified basin in this period. The basin experienced two evolutionary stages, respectively, the fore-arc depression basin in the Early–Middle Jurassic (J1-2) and the back-arc faulted basin in the Late Jurassic–Cretaceous (J3-K). There was considerable deposition of dark mudstones in the SECS during the Lower–Middle Jurassic. The Keelung Sag was the depositional center accumulating the thickest section of the Lower–Middle Jurassic source rocks which entered a high-maturity stage. Hence, it was the hydrocarbon generation center in the SECS. The process of generating hydrocarbons from Lower–Middle Jurassic source rocks was of high complexity from northwest to southeast. The Lower–Middle Jurassic source rock at the northwest edges of the basin experienced two hydrocarbon generation stages, while the Keelung Sag toward the southeast experienced three hydrocarbon generation stages. The models and types of oil–gas accumulation in various evolutionary phases were different due to the control by tectonic evolution. Oil and gas that were generated by Lower–Middle Jurassic source rocks in the Keelung Sag migrated and accumulated in the western high-tectonic units. Research findings provide insights into Mesozoic oil and gas exploration in the NSCS-SECS.